WSN-Based IoT Water Tank Monitoring with Accuracy and QoS Evaluation (ELKHA : Jurnal Teknik Elektro, 2026)
This study presents a Wireless Sensor Network (WSN)-based Internet of Things (IoT) water tank monitoring system designed to provide reliable real-time monitoring and performance evaluation. The proposed system utilizes NodeMCU ESP8266 modules and ultrasonic sensors to measure water levels across multiple tanks within a distributed WSN architecture. Previous studies on IoT-based water monitoring have largely focused on system implementation, conceptual frameworks, or application-oriented solutions, while comprehensive experimental validation of sensing accuracy and network communication performance is often limited. In particular, integrated evaluation approaches that simultaneously assess sensor measurement accuracy and network Quality of Service (QoS) performance in multi-node WSN deployments remain relatively underexplored. To address this gap, this study applies an integrated evaluation framework that combines ultrasonic sensing accuracy testing and QoS delay analysis, based on the Telecommunication and Internet Protocol Harmonization Over Networks (TIPHON) standard. Experimental results show that the system achieved average measurement accuracies of 96.59%, 97.21%, and 97.37% for Tanks 1, 2, and 3, respectively. Network performance evaluation under non-Line-of-Sight (non-LoS) indoor conditions produced an average transmission delay of 28.75 ms, which falls within the “very good” category according to TIPHON QoS criteria. These results demonstrate that the proposed WSN–IoT architecture provides reliable sensing performance and stable communication for domestic water tank monitoring applications.